2017
DOI: 10.1080/17470218.2016.1187182
|View full text |Cite
|
Sign up to set email alerts
|

Commission errors in delay–execute prospective memory tasks

Abstract: Individuals frequently retrieve an intention, but the execution of the task needs to be delayed due to ongoing task demands - so-called delay-execute prospective memory (PM) tasks. We investigated commission errors in the delay-execute paradigm. Participants were told that a PM task is finished (PM task has been executed and is now finished for a final phase) or cancelled (PM task has been cancelled immediately after introduction). We observed commission errors and ongoing task performance in the final phase w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
19
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 37 publications
3
19
1
1
Order By: Relevance
“…However, the effect of the inhibition measure could not be replicated in a subsequent study using an implementation intention encoding condition (Bugg et al, 2013), and the correlation between inhibition score and commission errors is limited to older adults (Scullin et al, 2011). Furthermore, Schaper and Grundgeiger (2017) observed commission errors in younger adults in the delay-execute paradigm. In this paradigm, there is a delay of 45 s between the PM cue and the window of opportunity for the associated action, during which the participants continue to work on the ongoing task.…”
mentioning
confidence: 96%
See 2 more Smart Citations
“…However, the effect of the inhibition measure could not be replicated in a subsequent study using an implementation intention encoding condition (Bugg et al, 2013), and the correlation between inhibition score and commission errors is limited to older adults (Scullin et al, 2011). Furthermore, Schaper and Grundgeiger (2017) observed commission errors in younger adults in the delay-execute paradigm. In this paradigm, there is a delay of 45 s between the PM cue and the window of opportunity for the associated action, during which the participants continue to work on the ongoing task.…”
mentioning
confidence: 96%
“…Once the intention is no longer relevant, either because the intention has been executed and declared finished, or it has been declared cancelled without being executed at all, after-effects may remain (Anderson & Einstein, 2017; Bugg, Scullin, & McDaniel, 2013; Walser, Fischer, & Goschke, 2012). Indeed, if the PM cue still occurred at a later point in time, researchers observed commission errors, that is, the erroneously repeated execution of the PM task following previously relevant cues (Bugg & Scullin, 2013; Schaper & Grundgeiger, 2017; Scullin, Bugg, & McDaniel, 2012). The dual mechanism account of commission errors (Bugg, Scullin, & Rauvola, 2016; Scullin & Bugg, 2013) states that commission errors are the result of spontaneous retrieval and subsequent failure to suppress the execution of the intention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The finding that commission error rates were nominally lower in the modified zero-target condition in Experiment 2 raises the possibility that another source is possible-participants may have pressed the Q key in the standard variant of this condition (e.g., Experiment 1a) because they thought the experimenter made an error upon being instructed not to perform the task "again." Considering past research that has demonstrated higher rates of commission errors in zero-target conditions that did not use phrasing such as the word again (see, e.g., Schaper & Grundgeiger, 2017, who told participants they could ignore the red screen in the finished phase because they were chosen for a condition that did not have to react to it) we also cannot rule out the possibility that the Experiment 2 commission error rate reflects sampling error. Thus, future studies should contrast the standard and modified versions head-to-head to determine the stability of this pattern.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This means participants cannot fulfill the intention. Although it may seem intuitive that a PM intention performed multiple times (as in the four-target condition) would become somewhat habitual and therefore be harder to deactivate than an intention that was never performed (as in the zero-target condition), the findings from these studies were quite the opposite (see also Schaper & Grundgeiger, 2017 ). For example, Bugg and Scullin ( 2013 ) found that participants in the four-target condition deactivated the intention and did not make a commission error (but see Pink & Dodson, 2013 ).…”
mentioning
confidence: 98%